2015
DOI: 10.1002/pat.3517
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of polyamidoamine dendrimer (PAMAM/CuS/AA) nanocomposite and its application in the removal of Isma acid fast yellow G Dye

Abstract: The adsorption of Isma acid fast yellow G dye was studied using polyamidoamine (PAMAM)/Copper sulfide (CuS)/AA nanocomposite containing different amounts of CuS by batch technique. PAMAM dendrimer/CuS/AA nanocomposites were synthesized via gamma irradiation cross‐linking method with the aid of sonication. The nanocomposites were characterized by Fourier‐transform infrared, X‐ray diffraction, transmission electron microscope, energy dispersive spectroscopy X‐ray, thermal gravimetric analysis, ultraviolet‐visibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 35 publications
(44 reference statements)
0
7
0
Order By: Relevance
“…In a typical method, gelatin/CuS/PVA nanocomposites were prepared according to the method reported in previous work by Abou Taleb, et al [20]. In Particular, 0.3 g of gelatin was dissolved in 30 ml of distilled water under ultrasonic stirring for 1 h at room temperature to form an aqueous solution of 1% concentration.…”
Section: Synthesis Of Gelatin/cus/pva Nanocompositesmentioning
confidence: 99%
See 1 more Smart Citation
“…In a typical method, gelatin/CuS/PVA nanocomposites were prepared according to the method reported in previous work by Abou Taleb, et al [20]. In Particular, 0.3 g of gelatin was dissolved in 30 ml of distilled water under ultrasonic stirring for 1 h at room temperature to form an aqueous solution of 1% concentration.…”
Section: Synthesis Of Gelatin/cus/pva Nanocompositesmentioning
confidence: 99%
“…The application of natural organic substances in the preparation of nano-sized material introduces a cutting edge for the charge transfer resulting in major enhancement of photocatalytic efficiency [18] [19]. Aboutaleb, et al [20] prepared PAMAM dendrimer/CuS/AA nanocomposites using gamma irradiation cross-linking method with the aid of sonication. They used the prepared materials to evaluate the removal of Isma acid fast yellow G Dye.…”
Section: Introductionmentioning
confidence: 99%
“…The results indicated that adsorption isotherm (26). In another study, nanocomposites including copper sulfide and PAMAM dendrimer were used to remove Isma acid fast yellow G dye, and the results indicated that adsorption obeyed Langmuir model and with pH increase, the rate of adsorption decreased (27).…”
Section: Evaluation Of Reactive Blue 19 Dye Adsorption Isothermmentioning
confidence: 99%
“…The dye‐contaminated water presents a serious environmental problem for both toxicological and esthetical reasons . Thus, in recent years, considerable attention has been paid on the removal of dyes from the contaminated waste water . By now, a wide range of physical and chemical techniques has been applied to control dye contamination such as oxidation, coagulation, biological treatment, and membrane filtration .…”
Section: Introductionmentioning
confidence: 99%
“…[1,2] Thus, in recent years, considerable attention has been paid on the removal of dyes from the contaminated waste water. [3][4][5] By now, a wide range of physical and chemical techniques has been applied to control dye contamination such as oxidation, [6] coagulation, [7] biological treatment, [7] and membrane filtration. [8] However, the adsorption technique has been found to be superior to other methods because of its simplicity of design, ease of handling, high efficiency, cost-effectiveness, and capability for absorbing a broad range of dyes.…”
Section: Introductionmentioning
confidence: 99%